Implementasi Pendidikan Agama Islam dalam Penguatan Profil Pelajar Pancasila di MIN 7 Ponorogo - Nisa, Yushfa Yufrida Nazzun; Ariyanto, Ayok; Syukroni, Azid (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Strengthening the character of the Pancasila student profile through the implementation of Islamic Religious Education is the right and crucial thing for students because with Islamic religious education it can form a solid moral and ethical basis in their daily lives and the character that is formed is not only an attitude that supports justice, harmony, tolerance but its Islamic character will also grow well. Islamic character will also grow well. Based on the object, this research uses a qualitative approach with a field type, namely research that goes directly to the field to obtain factual data with data collection techniques through observation and informant interviews that have characteristics relevant to the research. The aim is to find out the implementation of Islamic religious education in strengthening the student profile of Pancasila through habituation activities, habituation programs, and Islamic religious education. Pancasila through habituation activities, tahfidz programs and P5 lessons and then to find out how the results of the pancasila student profile character formed from the implementation for children both in the school environment and the community environment.